The Digital Transformation of the Television Industry - Londoño Proaño, Cristián (My University, 2025)
The study analyzes the digital transformation of the television industry, driven by digitalization and the emergence of streaming platforms. Its objective is to evaluate how this evolution has affected television production, distribution and consumption, using Albarrán’s model of the five external forces in the media industry. Through a qualitative approach and analysis of industry data, it is concluded that these five forces have profoundly transformed the television industry. Globalization has allowed the expansion of streaming platforms, regulation is still key to managing rights and concessions, and technology has revolutionized the production and distribution of content. In addition, audiences have become more active and personalized, presenting new challenges and opportunities for the industry in an ever-evolving environment.
Keywords: Digital televisión; industria de los medios; streaming; tecnología de la comunicación; televisión